Peningkatan Motivasi Pembelajaran Membaca Tabel Dan Grafik Menggunakan Pendekatan Contexstual Teaching And Learning di Sekolah Menengah Atas - Budi Santuso (Perkumpulan Pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya, 2021)
AbstractThis study aims to determine and analyze the motivation and learning achievement of class XII IPS 2 SMA Negeri Jenggawah students in the odd semester Indonesian language subject for the 2019/2020 school year after participating in learning with problem-solving methods. In addition, to determine the level of effectiveness in achieving the target of learning completeness. The approach used is Stephen Kemmis'